Learning Words in Two Languages: Manipulating Exemplar Variability for Within- and Cross-Language Generalization. - De Anda, Stephanie; Ellis, Erica M.; Mejia, Nayelli C. (Journal of Speech, Language & Hearing Research, 2022)
Purpose: This article aims to describe how exemplar variability can manipulate the word learning environment to maximize within- and cross-language generalization in Spanish--English bilinguals. Furthermore, we examined sources of individual variability that predicted word learning. Method: Nineteen Spanish--English bilingual children participated in a word learning task presenting words in both languages. Children learned words either in a high variability condition (in which multiple exemplars are introduced with the target word) or in a no variability condition (in which the same referent is used with the target word). Word learning was tracked over the course of the training, and retention was examined once the training was discontinued. Children's generalization of referents within and across languages was also examined. Results: The exemplar variability effect was observed in within-language generalization trials, whereas cross-language generalization was less robust. Nevertheless, cross-language associations emerged in examining the role of language proficiency, such that semantic skills in English predicted word retention across languages. Similarly, children's propensity to code-switch during language production was positively correlated with retention of words learned in the high variability condition. Conclusions: The findings show that Spanish--English bilingual children may make use of exemplar variability to support word learning in different ways compared with monolinguals. The exemplar variability effect interacts with children's acquired language skills and word learning abilities at the start of the intervention. This study provides preliminary evidence from which future research can develop word learning interventions that are responsive to the needs of multilinguals.